ПРОБЛЕМАТИКА ПРАВОВОЇ ПРИРОДИ РЕКОМЕНДАЦІЙНИХ РОЗ’ЯСНЕНЬ АНТИМОНОПОЛЬНОГО КОМІТЕТУ УКРАЇНИ - Podtserkovnyi, O.P.; Ziatina, D.V.; Khamkhodera, O.P. (V. Mamutov Institute of Economic and Legal Research of the National Academy of Sciences of Ukraine, 2021)
The article is devoted to the scientific analysis of legal nature of recommendation clarifications of Antimonopoly Committee of Ukraine. The detailed attention is paid to the thorough investigation of provisions of Recommended Clarifications of Antimonopoly Committee of Ukraine No. 39-pp August 08th, 2016 that defines the legal approaches of Anti monopoly Committee, which are recommended to apply by its official bodies while defining of fines for violation of legislation on protection of economic competition, including protection from unfair competition, in order to ensure the legal certainty and predictability of application of legal provisions. On the basis of scientific research, the conclusion is made that recommended clarifications of Antimonopoly Committee of Ukraine by their legal nature are the acts of common regulative force that are not the legislative acts, they also cannot create new legal provisions, they belong to the so called “soft law” by means of which the uniformity of interpretation and uniform rules for realization of legal provisions are ensured. The importance of recommendation as interpretation of legal provisions is highlighted, their place in the regulation of legal relations is defined. The main purpose of recommendations is to form the legal opinion of state authority abot the content and the order of execution of legal provisions. The authors make a conclusion that withdrawal of Antimonopoly Committee of Ukraine from its own legal position as to the practice of fine calculation, that is prescribed in recommended clarifications, provides the possibility to talk about the violation of one of the major principle of law — the principle of legal certainty. The proper realization of discretional competence is based on the compliance with the requirements of legality and adequacy of law enforcement decisions of empowered officials. With the purpose of improvement of current legislation, it is proposed to approve the Methodology for calculating the amount of fines by the Antimonopoly Committee of Ukraine for violation of the legislation on protection of economic competition. The adoption of such Methodological guidance for calculation of fines will increase the efficiency of national regulative provisions and goes completely in line with the provisions of Association Agreement between the European Union and Ukraine. REFERENCES 1. Shchodo zastosuvannia polozhen chastyny druhoi, piatoi ta shostoi statti 52 Zakonu Ukrainy “Pro zakhyst ekonomichnoi konkurentsii”, chastyn pershoi ta druhoi statti 21 Zakonu Ukrainy “Pro zakhyst vid nedobrosovisnoi konkurentsii”: Rekomendatsiini roziasnennia Antymonopolnoho komitetu Ukrainy vid 09.08.2016 № 39-rr. Ofitsiinyi sait Antymonopolnoho komitetu Ukrainy. URL: https://amcu.gov.ua/npas/rekomendacijni-rozyasnennya-shchodozastosuvannya-polozhen-chastin-drugoyi-pyatoyi-ta-shostoyi-statti-52-zakonu-ukrayini-pro-zahist-ekonomichnoyikonkurenciyi-chastin-pershoyi-ta-drugoyi-stat [in Ukrainian].2. Normatyvno-pravovi akty ministerstv, inshykh tsentralnykh orhaniv vykonavchoi vlady, pravovi aspekty yikh vykonannia ta zastosuvannia. Ofitsiinyi sait Ministrerstva yustytsii Ukrainy. URL: https://minjust.gov.ua/m/normativnopravovi-akti-ministerstv-inshih-tsentralnih-organiv-vikonavchoi-vladi-pravovi-aspekti-ih-vikonannya-tazastosuvannya[in Ukrainian].3. Koval V.M. Problemy zastosuvannia norm materialnoho prava v hospodarskomu sudochynstvi. Odesa: Yurydychna literatura, 2011. 528 p. [in Ukrainian].4. Rabinovych P.M. Osnovy zahalnoi teorii prava ta derzhavy. Lviv: Krai, 2007. 192 p. [in Ukrainian].5. Melnychuk S.M. Interpretatsiino-pravova forma realizatsii funktsii suchasnoi derzhavy Ukraina. Yurydychnyi naukovyi elektronnyi zhurnal. 2018. No. 6. P. 41-44. URL: http://www.lsej.org.ua/6_2018/10.pdf [in Ukrainian].6. Lepish N.Ia. Akty tlumachennia norm prava: pytannia teorii ta praktyky. Lviv: Spolom, 2018. 250 p. [in Ukrainian].7. Shalinska I.V. Oznaky ta vydy aktiv “miakoho prava”. Naukovyi visnyk Uzhhorodskoho natsionalnoho universytetu. Seriia “Pravo”. 2013. Issue 23. Chapter I. Vol. 1. P. 104-107 [in Ukrainian].8. Hrymaliuk P.O. Zahalnyi analiz aktiv “miakoho prava” (“soft law”) u pravi Yevropeiskoho Soiuzu. Prykarpatskyi yurydychnyi visnyk. 2014. Iss. 3. P. 340-349 [in Ukrainian].9. Kryvetska L.M. Yurydychna pryroda aktiv tlumachennia norm prava. Naukovyi visnyk Lvivskoho derzhavnoho universytetu vnutrishnikh sprav. Seriia yurydychna. 2011. Issue 4. P. 25-33 [in Ukrainian].10. Sanyakhmetova N.A. Klassyfykatsyia norm predprynymatelskoho prava. Pidpryiemnytstvo, hospodarstvo i pravo. 2001. No. 7. P. 20-22 [in Ukrainian].11. Venher V.M. Obmezhennia dyskretsiinykh ponovazhen yak skladova pryntsypu verkhovenstva prava. Naukovi zapysky. Yurydychni nauky. 2013. Vol. 144-145. P. 49-54 [in Ukrainian].12. Milash V.S. Mistse pidpryiemnytskoho komertsiinoho dohovoru v mekhanizmi pravovoho rehuliuvannia rynkovykh vidnosyn. Problemy zakonnosti. 2006. Iss. 77. P. 21-31 [in Ukrainian].13. Matvieieva Yu.I. Pryntsyp pravovoi vyznachenosti yak skladova verkhovenstva prava: dys. … kand. yuryd. nauk: 12.00.01. Kyiv, 2019. 220 p. [in Ukrainian].14. Yevropeiska Komisiia “Za demokratiiu cherez pravo” (Venetsiiska Komisiia). Mirylo pravovladdia. Komentar. Hlosarii. Per. S. Holovatoho; USAID. Kyiv, 2017. 163 p. URL: http://www.arbitr.gov.ua/files/pages/Mirylo_pravovladya.pdf [in Ukrainian].15. Zahalne administratyvne pravo: pidruchnyk. Za red. I.S. Hrytsenka. Kyiv: Yurinkom Inter, 2017. 568 p. [in Ukrainian].16. Kravtsova I. Shtraf za porushennia antymonopolno-konkurentnoho zakonodavstva yak vyd administratyvno-hospodarskoi sanktsii. Pidpryiemnytstvo, hospodarstvo i pravo. 2020. No. 7. P. 89-95 [in Ukrainian].17. Administratyvna protsedura ta administratyvni posluhy. Zarubizhnyi dosvid i propozytsii dlia Ukrainy. Avt.-uporiad. V.P. Tymoshchuk. Kyiv: Fakt, 2003. 496 p.18. Association Agreement between the European Union and its Member States, of the one part, and Ukraine, of the other part. Official Journal of the European Union. 29.05.2014. L 161/3. URL: https://trade.ec.europa.eu/doclib/docs/2016/november/tradoc_155103.pdf [in Ukrainian].19. Shvydka T.I. Ekonomichna konkurentsiia: suchasnyi stan zakonodavchoho zabezpechennia ta perspektyvy yoho modernizatsii. Kharkiv: Pravo, 2020. 376 p. [in Ukrainian].20. Proekt Zakonu pro vnesennia zmin do zakonodavstva pro zakhyst ekonomichnoi konkurentsii shchodo vyznachennia orhanamy Antymonopolnoho komitetu Ukrainy rozmiru shtrafiv za porushennia zakonodavstva pro zakhyst ekonomichnoi konkurentsii. Reiestr. No. 2431 vid 19.03.2015. Ofitsiinyi sait Verkhovnoi Rady Ukrainy. URL: http://w1.c1.rada.gov.ua/pls/zweb2/webproc4_2?pf3516=2431&skl=9 (data zvernennia: 15.03.2021).